Sales system's requirement analysis using structured system analysis and design method. Issue 1 (October 2020) - Mutiarasari US, Indah; Pontoh, Grace T.; Rahman, Abdul
Abstract: This study aims to analyze and evaluate the internal control of the sales system using the Structured Systems Analysis and Design Methods. Data Sources used are primary data collected directly through observation by carrying out daily activities at PT RRM. The data obtained were then analyzed based on the needs analysis module and the internal control evaluation indicators used in this study. The results showed that the current sales system applied at PT RRM still uses manual procedures and not enough internal physical control. There are several indicators of internal control that have not been implemented or are still felt to be lacking, especially in the authorization, access control, and segregation of duties. The study also produced five catalogs of needs, all of which were met in the proposed sales system design concept, which is an integrated sales system. The results of this study can improve the company's operational efficiency.